2016
DOI: 10.1016/j.worlddev.2015.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence on the Drivers of Index-Based Livestock Insurance Demand in Southern Ethiopia

Abstract: While index-based microinsurance has attracted considerable attention, uptake rates have been weak in many low-income countries. We explore the purchase patterns of index-based livestock insurance in southern Ethiopia, focusing on the role of accurate product comprehension and price. We find that randomly distributed learning kits improve subjects' knowledge of the products; however, we do not find strong evidence that the improved knowledge per se causes greater insurance uptake. We also find that reduced pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 52 publications
4
54
0
Order By: Relevance
“…In each period, a randomly selected 20% of sample households did not receive a coupon. 3 Takahashi et al (2016) examine factors affecting IBLI uptake in our study area and found that the distribution of discount coupons significantly increases uptake of IBLI. Thus, randomized receipt of a discount coupon serves nicely as an instrument for IBLI uptake.…”
Section: Study Design and Summary Statisticsmentioning
confidence: 98%
“…In each period, a randomly selected 20% of sample households did not receive a coupon. 3 Takahashi et al (2016) examine factors affecting IBLI uptake in our study area and found that the distribution of discount coupons significantly increases uptake of IBLI. Thus, randomized receipt of a discount coupon serves nicely as an instrument for IBLI uptake.…”
Section: Study Design and Summary Statisticsmentioning
confidence: 98%
“…Regarding the role of product comprehension, Takahashi et al . () come to the conclusion that improved knowledge about IBI per se does not necessarily increase demand. However, they find strong evidence for price effects in their data from Ethiopia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors conclude that information about insurance payouts have villagewide demand effects. Regarding the role of product comprehension, Takahashi et al (2016) come to the conclusion that improved knowledge about IBI per se does not necessarily increase demand. However, they find strong evidence for price effects in their data from Ethiopia.…”
Section: Literature Reviewmentioning
confidence: 99%